2019
DOI: 10.1186/s40691-018-0169-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weft yarn twist level on mechanical and sensorial comfort of 100% woven cotton fabrics

Abstract: Fabric sensory properties are complex concepts which include dimensional changes at small forces such as tensile, shear, compression and bending, surface properties (friction and roughness) plus surface coolness or warmness. The aim of this study was to investigating the effect of weft yarn twist level on sensorial comfort of 100% woven cotton fabrics. Five cotton fabrics were woven with incremental weft yarn twist levels and their tensile and shear strength, pure bending, compression, surface friction and rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…Th is is because of the higher number of turns per meter, which contributes to resistance to the applied load (undamaged) and easier recovery. Th is result is confi rmed by a previous similar report on the recoverability of knitted fabrics [15] and the bending properties of woven fabrics [13].…”
Section: Wrinkle Recoverysupporting
confidence: 85%
See 1 more Smart Citation
“…Th is is because of the higher number of turns per meter, which contributes to resistance to the applied load (undamaged) and easier recovery. Th is result is confi rmed by a previous similar report on the recoverability of knitted fabrics [15] and the bending properties of woven fabrics [13].…”
Section: Wrinkle Recoverysupporting
confidence: 85%
“…It was observed that bending, shear and aerial density aff ect drape characteristics [2,4]. Th e eff ect of yarn parameters on the mechanical properties (at low-stress) of woven fabrics, tensile strength, compression, bending and shear property were studied by the authors of this work [13]. Th ough many researchers have studied the eff ect of yarn parameters such as count and twist on tactile comfort, and on drape, tensile and stiff ness properties, most of the studies were done at the grey fabric level.…”
Section: Introductionmentioning
confidence: 95%
“…Air permeability is one of the most important characteristics in the functioning of fabrics for facial mask in the prevention of air borne diseases as they aid as This study shows that yarn twist of the woven fabrics contribute significantly to increase in circular and density of the fabric simultaneously decreasing the diameter and further increasing the high rate of air passage [23], it records about 2800 Pa. Also, yarn crimp demonstrate high rate of fabric opening causing extension, increase in free space which permit high air permeability. In yarn construction, yarns are modified by increasing the twist for special effect, this correspondingly permit spherical, and high-density yarns to be crammed tightly together in complex woven structure with much lower air permeability.…”
Section: Resultsmentioning
confidence: 84%
“…This can be explained based on the fact that the high twisted yarns are compact enough to behave like a unit. When twisted yarn lies on another twisted yarn, it always is supposed to leave the highest free space between the yarns [3]. Flat filament configuration with zero-twist registered a significant reduction in air permeability in comparison to twisted warp fabrics.…”
Section: Air Transmissionmentioning
confidence: 96%